Struktura makrocyklu treningowego w biegu na 100 m przez płotki = The structure of the training macrocycle in the 100 m hurdles - Kamrowska-Nowak, Maria; Byzdra, Krzysztof; Stępniak, Robert (Journal of Education, Health and Sport, 2015)
Kamrowska-Nowak Maria, Byzdra Krzysztof, Stępniak Robert. Struktura makrocyklu treningowego w biegu na 100 m przez płotki = The structure of the training macrocycle in the 100 m hurdles. Journal of Education, Health and Sport. 2015;5(12):333-344. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35485 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A333-344 http://pbn.nauka.gov.pl/works/682446 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 15.12.2015. Accepted: 17.12.2015. Struktura makrocyklu treningowego w biegu na 100 m przez płotki The structure of the training macrocycle in the 100 m hurdles Maria Kamrowska-Nowak, Krzysztof Byzdra AWFiS Gdańsk, Zakład LA Robert Stępniak UKW w Bydgoszczy, IKF Streszczenie Celem badań była analiza struktury czasowej oraz charakterystyka obciążeń treningowych płotkarki w rocznym cyklu, zrealizowanych przez zawodniczkę specjalizującą się w biegu na 100 m przez płotki. Materiał badawczy stanowiła dokumentacja szkolenia i obciążeń treningowych zawodniczki S.G., mistrzyni Polski juniorek z 1999 r. oraz młodzieżowej mistrzyni Polski z 2000 r. Zebrany materiał dotyczący obciążeń treningowych skatalogowano według klasycznego podziału ćwiczeń ze względu na cechy motoryczne. Przygotowania treningowe do cyklu 1999/2000 trwały 336 dni. Zrealizowano 367 jednostek treningowych. W przygotowaniu siłowym największe obciążenie miało charakter ukierunkowany o przewadze półprzysiadów oraz podskoków i wyskoków z półprzysiadu. Siła o charakterze wszechstronnym miała mniejszy wymiar. Największe obciążenie pracą siłową miało miejsce od marca do czerwca. W okresie przygotowania ogólnego (listopad, grudzień, styczeń) dominowała wytrzymałość tempowa krótka (odcinki 150 -300m), a następnie wytrzymałość szybkościowa, która ma wpływ na utrzymanie rytmu płotkowego od 7 do 10 płotka. Szybkość techniczna realizowana była od listopada do września, a najwięcej zrealizowano w miesiącach marcu i kwietniu. Słowa kluczowe: lekkoatletyka, kobieta, bieg na 100 m przez płotki. Summary The objective of the research was to analyze time structure and characteristics of training loads of the hurdler specializing in 100m hurdles realized in the annual training cycle. Training records and training loads of S.G. , the junior champion of Poland in 1999 and the youth champion of Poland in 2000, constituted research material. Material concerning training loads was catalogued according to classical division of exercises on account of motor features. Preparations for the training cycle 1999/2000 lasted 336 days, and 367 training units were carried out. In weight preparation the greatest load was task oriented with a predominance of half knee bends, jumps and a jump from half knee bands. Strength of versatile nature had minor dimension. The greatest loads of weight training took place between March and June. During general preparation (November, December, and January) a short pace endurance dominated (segments 150-300 m), and was followed by speed endurance; the latter having influence on keeping rhythm from 7 to 10 hurdles. Technical speed was realized between November and September and the greatest number of tasks was carried out in March and April. Keywords: athletics, woman, women’s 100 m hurdles.